Narečje v projektnem učenju - Ljubešić, Marko (Jezik in slovstvo, 2015)
In order to change the approach towards teaching the native language in the Croatian school system, which neglects the student's (dialect) idiom, a methodical model based upon the project method system is proposed. Taking as a starting point the principles of homeland, appropriateness, actualisation and interest, on the one hand, and the correlative-integrative relations between the related subjects, on the other, the authors establish a new paradigm in the teaching of standard language.
Keywords: Croatian; hrvaščina; dialect; narečja; knjižni jezik; standard language; projektno učenje; jezikovna didaktika